ANALISA TERHADAP BATASAN TANGGUNG JAWAB DIREKTUR NOMINEE DALAM PERSEROAN TERBATAS - Sugondo Sugondo (PREMISE LAW JURNAL, 2013)
The assignment of nominee director in a Limited Liability Company becomes one of the options which is currently chosen nowadays. Nominee director is someone who appointed as a director, or his name is borrowed by a certain party, and directed to run a company in accordance with the direction of those who appointed him/her and borrowed his/her name. In terms of a Director in his/her capacity as Nominee, the regulation for this practice continues to be regulated as for the non-nominee director as stated in the Indonesia Law Number 40 of Year 2007 regarding the Limited Liability Company. A nominee Director has the same responsibility as that of a non-nominee director, including full responsibility for the company’s damages in case of the nominee director is guilty or found negligent in performing his/her duties. This is closely related to the implementation of business judgment rule principle, especially in case that the nominee director must be able to prove that in managing the company, he/she with the principle of prudent man rule always prioritizes the standard of due of care, due of loyalty, and the principle of no conflict of interest. The nominee director is required to make sure that the interest of company must be put in the first priority for whatever reason, and paired with the interests of the minority shareholders and the stakeholders. Keywords: Nominee Director, Responsibility, Limited Liability Company